Epithelial-mesenchymal transition (EMT): principles and clinical impact in cancer therapy. - Franco Chuaire, María Liliana; Sánchez Corredor, Magda Carolina; Chuaire Noack, Lilian (Investigación Clínica, 2013)
The epithelial-mesenchymal transition (EMT) is a biological phenomenon responsible for the formation of different tissues and organs during normal metazoan development. Because of the connection of the EMT with the pathogenesis of certain diseases, such as cancer, the attention of the scientific community has been directed towards the search for and identification of effective therapeutic targets. These targets include signal transduction in cancerous stem cells and the use of microRNAs, which would inhibit EMT-associated phenotypic changes and tumoral progression. In an attempt to compile relevant and current information, this work addresses concepts that define the EMT and the advances in this field. The wealth of knowledge gained from areas such as the loss of cell polarity and intracellular adhesion complexes, the signaling pathways implicated, microRNA participation in this process, and stemness acquisition in embryonic and cancerous cells, all of which allow for the visualization of promising perspectives, particularly, methods for targeting advanced malignancies, are presented herein.